Survival Study of Extreme Record - Adam, Mohd Bakri (Institute for Mathematical Research, 2008)
This paper describes the survival study of extreme record of athletics performance. Two area of statistics are used to model and check the best model for the athletics data. We make use of the extreme value theory for minima and utilized the facility provided by the Kaplan-Meier to develop new goodness-of-fit test method via graphical approaches.